The impact of AI-powered robotics and workforce dynamics on productivity in the logistics industry - Periasamy, Usha A/P; Senathirajah, Abdul Rahman Bin S; Soliman, Karim; Haque, Rasheedul; Lertatthakornkit, Tippawan (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of AI-powered robotics and workforce dynamics on productivity in the logistics industry, drawing on insights from existing literature. The logistics sector is well-suited for AI integration due to its reliance on repetitive tasks, supply chain efficiency, and operational scalability. Early findings suggest that AI-driven robotics can enhance productivity by improving inventory management accuracy, streamlining transportation, and reducing operational costs. However, workforce dynamics also play a crucial role, as employees must adapt to new technological roles, acquire new skills, and collaborate with robotic systems, which can impact job satisfaction, motivation, and overall efficiency. Additionally, employee adaptability acts as a moderating factor, determining how effectively companies can leverage AI technologies to boost productivity. This literature review highlights the need for further empirical research to validate these relationships and provide actionable insights for logistics companies aiming to optimize operations, enhance human-robot interactions, and improve productivity outcomes.